Leaf anatomy of young legume trees from Cerrado as a support to the taxonomy - Longhi, Lucas Baltazar [UNESP]; Teruya, Guilherme Matsubara [UNESP]; Carneiro, Tainah Eduarda Boian [UNESP]; Paiva, Wesller da Silva de [UNESP]; Martins, Aline Redondo [UNESP] (Springer Nature, 2024)
Anatomical analyses of leaflets from 20 species of legume trees native to Cerrado were conducted using optical microscopy and scanning electron microscopy, seeking to identify anatomical characters that can assist in their taxonomic classification. All the analyzed species exhibited a uniseriate epidermis and collateral vascular system. All of them presented a dorsiventral mesophyll. The epidermis is predominantly papillose, and observed in some species, which is mainly evidenced in Erythrina mulungu, Erythrina falcata, and Senna alata. Except for Bauhinia variegata, Erythrina mulungu, Erythrina falcata, Erythrina verna, Hymenaea courbaril, and Inga laurina, the species showed long cells in the palisade parenchyma. The spongy parenchyma varied in terms of the size of intercellular spaces. Secretory cavities were present in Hymenaea courbaril, and prismatic calcium oxalate crystals were found in the mesophyll of Anadenanthera colubrina and Senegalia tenuifolia. Prismatic crystals were also present in the midrib of Anadenanthera colubrina, Anadenanthera peregrina, Pterocarpus violaceus, and Senegalia tenuifolia. Wax deposition was observed in all species, primarily in the form of plates. Glandular and non-glandular trichomes were identified. Hypostomatic and amphistomatic leaflets were observed, with the paracytic stomata type being the most common. The traits found in the present study corroborate with other studies conducted in Leguminosae reinforcing that anatomical analyses can be useful in the taxonomic characterization of species.
Keywords: Brazilian savannah; Fabaceae; Plant anatomy; Young tree